Analisis kerapatan jaringan pengukur curah hujan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT: In Indonesia, the purpose of planning a rainfall station which is to conduct hydrometeorological observations over a river basin (SWS) is to achieve only the depth of rainfall but not for deciding the station network Several methods have been developed for deciding the number of rainfal lnstalations. Kagan (1972) had developed the method for deciding not only for the number of rainfall stations but also the station network (pattern and density). In this study the Kagan method has been applied for deciding the station networks for 14 river basins in Jawa island. The analysis result shows that each SWS in Jawa island needs 9 and 10 rainfall stations for permissible error of 10 percent and 5 percent, respectively, based on monthly rainfall.